On weak ?-statistical convergence of order ? - Ercan, Sinan; Altin, Yavuz; Bektaş, Çi?dem A. (Politechnica University of Bucharest, 2018)
In the present paper, we give the concept of weak ?-statistical convergence of order ? and weakly [V,?]-summability of order ?. Some relations between of these concepts and also some relations between weak ?-statistical convergence of order ? and strong ?-statistical convergence of order ? are examined. © 2018 Politechnica University of Bucharest. All rights reserved.
Keywords: Cesàro summability; Weak statistical convergence